Taxonomic Reconciliation of Smilacaceae in the Indian Subcontinent: Synonymy, Typification, Updated Inventory, and a Vegetative Key for Identification - Sukhramani, Geetika; Choudhary, Ritesh Kumar (Phytotaxa, 2023)
Smilax is the sole genus of the family Smilacaceae, represented by 36 taxa in the Indian subcontinent. The taxonomy of the genus has been challenging due to its dioecious nature and substantial inter- and intra-specific variations. With an aim to clarify and streamline the nomenclature of Smilax species and resolve long-standing taxonomic ambiguities, a critical morphological analysis of the taxa belonging to Smilacaceae in the Indian subcontinent was carried out. We devised a key to the Smilax species of the Indian subcontinent based on vegetative characters alone, which will help in field identification throughout the year. Moreover, an updated checklist of the Smilacaceae in the Indian subcontinent is provided. In addition, Smilax aspericaulis and S. quadrumbellata are synonymized under S. odoratissima and S. zeylanica, respectively. The typification of four Smilax names is also addressed.